Adverse outcomes in non-fatal use of force encounters involving excited delirium syndrome. (4th May 2022) - Baldwin, Simon; Blaskovits, Brittany; Hall, Christine; Lawrence, Chris; Bennell, Craig
ABSTRACT: This study examined the risk of adverse outcomes during non-fatal encounters with subjects exhibiting features of Excited Delirium Syndrome (ExDS). Data for the study was collected over a five-year period through standardized reporting in a large Canadian law enforcement agency. Consistent with previous research, the presence of six or more of the ten features of ExDS was used to identify a probable case. Force was applied on 10, 718 subjects, 197 (1.8%) of which were probable ExDS. Logistic regression were used to model the odds that use of force (UoF) interventions used on subjects in a state of probable ExDS resulted in adverse outcomes. Probable ExDS was one of the most important predictors of adverse outcomes in UoF encounters, even after controlling for associated risk factors. There were significantly higher odds that UoF was ineffective on subjects exhibiting more features of ExDS, resulting in an increased amount of force applied. In contrast, there were significantly lower odds of injury from UoF for individuals exhibiting probable ExDS. Officers, however, were at a higher risk of injury when dealing with those displaying a greater number of features. These results underscore the risks inherent to incidents involving cases of probable ExDS. A greater understanding of such risks may improve response strategies and promote public and police safety.